T Cells Engaging the Conserved MHC Class Ib Molecule Qa-1b with TAP-Independent Peptides Are Semi-Invariant Lymphocytes - Doorduijn, Elien M.; Sluijter, Marjolein; Querido, Bianca J.; Seidel, Ursula J. E.; Oliveira, Claudia C.; van der Burg, Sjoerd H.; van Hall, Thorbald (Frontiers in Immunology, 2018)
The HLA-E homolog in the mouse (Qa-1b) is a conserved MHC class Ib molecule presenting monomorphic peptides to germline-encoded natural killer receptor CD94/NKG2A. Previously, we demonstrated the replacement of this canonical peptide by a diverse peptidome upon deficiency of the TAP peptide transporter. Analysis of this Qa-1b-restricted T cell repertoire against these non-mutated neoantigens revealed characteristics of conventional hypervariable CD8+ T cells, but also of invariant TCRαβ T cells. A shared TCR Vα chain was used by this subset in combination with a variety of Vβ chains. The TCRs target peptide ligands that are conserved between mouse and man, like the identified peptide derived from the transcriptional cofactor Med15. The thymus selection was studied in a TCR-transgenic mouse and emerging naïve CD8+ T cells displayed a slightly activated phenotype, as witnessed by higher CD122 and Ly6C expression. Moreover, the Qa-1b protein was dispensable for thymus selection. Importantly, no self-reactivity was observed as reported for other MHC class Ib-restricted subsets. Naïve Qa-1b restricted T cells expanded, contracted and formed memory cells in vivo upon peptide vaccination in a similar manner as conventional CD8+ T cells. Based on these data, the Qa-1b restricted T cell subset might be positioned closest to conventional CD8+ T cells of all MHC class Ib populations.